1-Dimensional analysis of land subsidence in Semarang city due to anthropogenic forces. Issue 1 (June 2021) - Sarah, D.; Soebowo, E.; Satrio, N. A.; Syahbana, A. J.; Wirabuana, T.; Wahyudin
Abstract: Anthropogenic factors play an important role in land subsidence. The northern part of Semarang City has long suffered from land subsidence since the 1980s. This paper aims to analyze the land subsidence process inthe northern part of the Semarang city due to anthropogenic factors of groundwater exploitation andbuilding loads. The analysis was carried out by using 1-dimensional numerical and analytical models. Results of modeling were subsequently compared to results from stable benchmark monitoring data in Madukoro and Kaligawe. Modeling results show that the contribution of groundwater level decrease accounts for 74-82% of the total subsidence, while the remaining 18-26% is attributed to the building load. The rate and magnitude of subsidence arehigher at thenortheastern part (Kaligawe) due to the thicker aquitard and more rapid groundwater level drop. Comparison of modeling and monitoring results signifies that the land subsidence in the northwestern part (Madukoro) approximately follows the model scenarios of groundwater level drawdown and surface loading;meanwhile the land subsidence rate in Kaligawe exceeds modeling results, most possibly due to the large discrepancy between the current conditions to modeling scenarios, presumably faster groundwater drawdown